Energetics of fast- and slow-twitch muscles of the mouse. - Barclay, C J (1993)
1. The energetic cost of work performance by mouse fast- and slow-twitch muscle was assessed by measuring the rates of thermal and mechanical energy liberation of the muscles at 21 degrees C. Thermal energy (heat) liberation was measured using a fast-responding thermopile. 2. Bundles of muscles fibres from the slow-twitch soleus and fast-twitch extensor digitorum longus (EDL) muscles were used. Work output was controlled by performing isovelocity shortenings during the plateau of an isometric tetanus. A range of shortening velocities, spanning the possible range, was used for each muscle. 3. During tetanic contractions, the rate of heat production from EDL muscle was 134.2 +/- 11.4 mW/g. The rate of heat production by soleus muscle was only one-fifth as great (26.8 +/- 2.7 mW/g). 4. The maximum shortening velocity (Vmax) of EDL muscles was 2.5-fold greater than that for soleus muscles and it's force-velocity relationship was less curved. Peak power output from EDL muscles was 3-fold greater than that from soleus muscle. 5. During shortening, the rate of heat output from soleus muscles increased considerably above the isometric heat rate. In contrast to soleus muscle, the rate of heat production by EDL muscle increased by only a small fraction of the isometric heat rate. The magnitude of the increases in rate was proportional to shortening velocity. 6. The total rate of energy liberation (heat rate + power) by EDL muscle, shortening at 0.95 Vmax was 1.62 +/- 0.37 times greater than the isometric heat rate. In contrast, the rate of energy liberation from soleus muscle shortening at 0.95 Vmax was 5.21 +/- 0.58 times greater than its isometric heat rate. The peak mechanical efficiency (power/total energy rate) of the both muscles was approximately 30%.